Political Violence, Organized Crimes, Terrorism and Youth - Ulusoy, M. Demet (IOS Press, 2013)
On October 3, 2002, The World Health Organization (WHO) released World Report on Violence and Health 1 as a most important issue for the millennium on October 3, 2002. This report examines what is known about the epidemiology and prevention of violence from research and programs throughout the world. It addresses several types of violence, including child abuse and neglect by caregivers, youth violence (violence by adolescents and young adults aged 10-29 years), intimate partner violence, sexual violence, elder abuse, self-inflicted violence, and collective violence (the use of violence by one group against another to achieve political, social, or economic objectives; for example, war or terrorism). In our study we will focus on collective violence which is planned to achieve or motivated by specific social, political or economic objectives of an organized social or political group 2 . In other words, the descriptive features of this type of violence are being sponsored by some power agents in societies or states.